ISOLASI, SELEKSI DAN IDENTIFIKASI BAKTERI PELARUT FOSFAT DARI TANAH RHIZOSFER TANAMAN TEH - , PUPUT PUTRI N ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Phosphate solubilizing bacteria (PSB) is a group of bacteria that have the ability to dissolve insoluble inorganic phosphate compounds, such as tricalcium phosphate, dicalcium phosphate, hydroxyapatite, and rock phosphate. The purpose of this study was to isolation, selection, and identification of PSB from the rhizosphere soil of tea plants. PSB isolated from the rhizosphere of tea plants in the clone 4 PGL11, PGL4, TRI 2025 and Gambung 3 taken from PT . Pagilaran, Batang, Central Java. Obtained isolates were tested for their ability to dissolve tricalcium phosphate in a liquid medium. BOXAIR - PCR was used to determine the PSB for further characterized. Sequencing of 16S rRNA gene was used to identify the selected PSB. Twenty PSB which formed clear zones around colonies on Pikovskaya agar medium were obtained in this study. Based on clear zone formation and origin of isolates, 13 isolates were selected to test his ability to dissolve phosphate quantitatively. Inoculation of 13 selected isolates in Pikovskaya liquid media lowered pH of the medium and the ability to dissolve phosphate was between 107.2 to 203.7 Âµg/ml after incubation for 48 hours. BOXAIR analysis - PCR revealed six different PCR profiles on the degree of similarity of 70%, which reflects the high diversity of genotypes between PSB obtained. Based on 16S rRNA gene sequencing results from six different isolates of genotype, showed that the five isolates had high similarity with Burkholderia and one isolate had a high similarity with the Serratia.